Efficient Electrochemical Reduction of Oxygen Catalyzed by Porous Carbon Containing Trace Amount of Metal Residues. Issue 11 (21st September 2018) - Feng, Xin; Dong, Xiaomei; Zhang, Qingcheng; Cui, Cuixia; Zhang, JingJing; Chen, Zhen; Wu, Changmi; Jin, Huile; Wang, Shun; Wang, Jichang
Abstract: In this study carbon materials with a hierarchical pore structure have been fabricated through a scalable and template free solvothermal method in the presence of metal catalysts, where the presence of metal catalysts was found to be essential for the initial polymerization process. The as‐prepared carbon contained trace amounts of metal residues and exhibited highly efficient catalytic activity toward the oxygen reduction reaction (ORR). Among all the metal catalysts studied, cobalt containing porous carbon exhibited the highest ORR electrocatalytic activity with great tolerance to methanol crossover and excellent long‐term cycling stability, outperforming the commercial 30 % ( w / w ) Pt/C catalysts. The great performance may be contributed to the unique porous structure, the large specific surface area of cobalt‐doped carbon and chemical activity of cobalt. The result provides useful guidance for the development of carbon‐based electrocatalysts. Abstract :